Wolf-Heidegger's atlas of human anatomy. - Köpf-Maier, Petra, ....- (Basel : Karger, 2005)
The 6th edition of Wolf-Heidegger's Atlas of Human Anatomy has been further revised, expanded and updated by Professor Petra Köpf-Maier. A well-established classic, the atlas has been renowned for the high quality of its illustrations since its inception; the more recent editions, however, have also received praise for their didactic structure and clinical approach. All illustrations are in color and are complemented in a highly instructive manner by a generous number of anatomical sections and selected radiological images (ultrasound, CT scans, MRIs). Placing these side by side serves to develop and train the skills needed to interpret these images correctly. New clinically relevant illustrations have been included and are shown within their practical context, ranging from herniated disks and paralysis symptoms to the consequences of a stenosed portal vein. Furthermore, the chapter on head and neck anatomy, which is of specific interest to dental students, has been enlarged. The atlas employs the current Terminologia Anatomica and introduces the most important eponyms, since they form an important part of daily clinical communication. Wolf-Heidegger's Atlas of Human Anatomy has been designed and crafted explicitly for students of human medicine and dentistry in their preclinical and clinical years, but will also appeal to clinical practitioners, who will appreciate the illustrations' superb quality and beauty as well as their continuing relevance to daily practical decision-taking.
Dl. 1: Systemic anatomy, body wall, upper and lower limbs (ISBN 3-8055-7667-6). Dl. 2: Head and neck, thorax, abdomen, pelvis, CNS, eye, ear (ISBN 3-8055-7668-4)
Keywords: Anatomie